Zachowania etyczne nauczycieli = Teachers` ethical behaviour - Zajdel, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article describes the ethical conditions for the practice of giving gifts to teachers that takes place in schools. These issues are not regulated by law, but by certain customs and traditions. Active teachers and potential teachers, i.e., senior students, have a di?erent attitude towards ethical norms. The authors hope that this article o?ers a deeper insight into the ethical conditions of giving gifts in institutions.
Keywords: etyka zachowań nauczycielskich; prezenty szkolne; dawanie dowodów wdzięczności; teachers` ethical behaviour; school gifts; giving evidence of gratitude